Inheritance and Comparison of Phenotypic Characters from Hybrid Chicken GK-Bro (Gallus gallus Linnaeus, 1758) - Damayanti, Putu Ayu; Daryono, Budi Setiadi; Mahardhika, I Wayan Swarautama (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2019)
GK-Bro (Gallus gallus Linnaeus, 1758) is a hybrid chicken from crossing between ♀ F2 Broiler ♂ F2 Golden Kamper that have variation of phenotypic character. To meet the market’s demand, GK-Bro must have prime phenotypic character in both quantity and quality. This research aims to examine the phenotype character that occur in GK-Bro by the character of feet morphometry, crest’s shape, feather’s color, and feet’s color. The parental chicken are crossed in Innovation and Agriculture Centre of Gadjah Mada University (Indonesia) and produce 11 chickens with five males and six females filial. The filial are maintained intensively and qualitative data were observed at the end of seven weeks, classified based on the percentage of the phenotypic class. Quantitative characters that observed were tibia and femur length after seven weeks, using control pelung, broiler, and F1 broiler. Quantitative data showed that the average length of the tibia and femur of GK-Bro is lower when compared to the control but the ratio of feet morphometry is closer to pelung. Qualitative data classified crest form in one class, feather’s color in 4 classes and feet’s color in 3 class.